If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 = 3x + -6x + 18 Reorder the terms: -3 = 18 + 3x + -6x Combine like terms: 3x + -6x = -3x -3 = 18 + -3x Solving -3 = 18 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -3 + 3x = 18 + -3x + 3x Combine like terms: -3x + 3x = 0 -3 + 3x = 18 + 0 -3 + 3x = 18 Add '3' to each side of the equation. -3 + 3 + 3x = 18 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = 18 + 3 3x = 18 + 3 Combine like terms: 18 + 3 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| 4y-8x=10 | | 55x-11y=253 | | -3(8-11j)=-5(12-j) | | -5d+19-4d=-6(4d+19)-4d | | 8x-15-4x=13 | | 15x+(15)=6 | | 5(-6n+3)=165 | | -4(-18+6n)=-6(13n+15) | | 3x-7=14+2 | | 4x-4-x=-4 | | 11-3s=8 | | 1(-7x+1)=-55 | | 5(-6+3)=165 | | y=3sinx+-4 | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.16 | | 7x-3-6x=3 | | (3y-28)/7=y/3 | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.16t | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.6t | | 7x+(10)=3 | | (x-28)/7=y/3 | | -5(5x+3)=45 | | 30(c+4)=900 | | 21=x-87+2x | | -19.82+18.5b=-9(-3b-12.72) | | X+0.16X=9600 | | 9(x-3)+3=-15 | | (10+5)*(30+6)=15+36 | | -6x-7x+4=5 | | 21(n+22)=945 | | N-1-3=-1 | | 2m+4n=12 |